Design, synthesis, biological evaluation, and nitric-oxide release studies of a novel series of celecoxib prodrugs possessing a nitric-oxide donor moiety - Wael Mohamed Soliman; Khaled Rashad Ahmed Abdellatif; Edward Elmer Knaus (Universidade de São Paulo, 2019)
A new group of hybrid nitric oxide-releasing anti-inflammatory drugs (NONO-coxibs), in which an O 2-acetoxymethyl-1-(N-ethyl-N-methylamino)diazen-1-ium-1,2-diolate NO-donor moiety is attached directly to the carboxylic acid group of 1-(4-aminosulfonylphenyl)-5-aryl-1H-pyrazol-3-carboxylic acids (6a-c), were synthesized. A low amount of NO was released from the diazen-1-ium-1,2-diolate compounds 6a-c upon incubation with phosphate buffer saline (PBS) at pH 7.4 (range: pH 7.97-8.51), whereas, the percentage of NO released was significantly higher (84.5%-85.05% of the theoretical maximal release of two molecules of NO/molecule of the parent hybrid ester prodrug) when the diazen-1-ium-1,2-diolate ester prodrugs were incubated in the presence of rat serum. These incubation studies demonstrated that both NO and the anti-inflammatory 1-(4-aminosulfonylphenyl)-5-(4-H, 4-F or 4-Me-phenyl)-1H-pyrazol-3-carboxylic acid (4a-c) would be released from the parent NONO-coxib upon in vivo cleavage by non-specific serum esterases. The parent compounds 4a-c displayed good anti-inflammatory effects (ID50=81.4-112.4 mg/kg p.o.) between those exhibited by the reference drugs, aspirin (ID50=114.3 mg/kg p.o.) and celecoxib (ID50=12.6 mg/kg p.o.). Hybrid ester anti-inflammatory/NO-donor prodrugs (NONO-coxibs) offer a potential drug-design concept directed toward the development of anti-inflammatory drugs that are lacking adverse ulcerogenic and/or cardiovascular effects.